Fundamentals of Yoga Meditation: Physical and Mental Benefits - Wazir C. Vasudeva (Recent Trends in Arts and Social Studies Vol. 5, 2023)
Yoga is a psycho-somatic-spiritual discipline for achieving union and harmony between our mind, body, and soul and the ultimate union of our individual consciousness with the universal consciousness. There are certain elements of meditation which should be achieved before sitting for meditation and are described. Transcendental meditation (TM) is one of the techniques of meditation, which involves allowing the mind to dwell on a series of words (called a mantra) given by the meditation teacher, with no effort. If the attention wanders it is allowed to wander till it returns to the mantra. A mantra is a sacred word or phrase that is chanted repeatedly in order to alter one’s state of mind and have miraculous religious and spiritual effects on the mind. When mantras are recited during meditation, people enter a higher state of consciousness. It is believed that chanting mantras opens the gates to the absolute. The sound of mantras is associated with a state of tranquil meditation which generates calmness, quietness, and peace in the mind and relaxes the muscles and tones the nervous system and becomes the cause for lowering blood pressure, heart rate, and rate of breath. This creates brain waves which deal with stress and its consequences. The opinion of several yoga masters and distinguished medical experts who worked on meditation for decades is expressed.